Computational human geography: towards a research agenda. - Openshaw, Stan (Environment & Planning A, 1994)
Scientific and technological opportunities in geography will be created by the new computational era that is soon likely to exist. The main methods used at the research frontiers of science have become increasingly computation dependent. The changes in these methods go far beyond the hard sciences and have the most profound implications for geography and most social sciences. These developments constitute an argument for the development of a computational human geography, a new computationally intensive and completely computer-dependent paradigm in geography.